Adsorptive removal of chromium (VI) from synthetic waters using magnetic lignocellulosic composites. Issue 1 (November 2021) - Medina-Espinosa, Tanya; Asimbaya, Christopher; Galeas, Salomé; Rosas-Laverde, Nelly M.; Debut, Alexis; Guerrero, Víctor H.
Abstract: The removal of heavy metals from water is one of the major challenges that humanity must address to avoid negative potential impacts on the environment and human health. During the last few years, several adsorbents have been examined, in a search for highly efficient and cost-effective materials. In this work, we investigated the use of laurel, canelo and eucalyptus lignocellulosic sawdust residues (LRs) impregnated with magnetite nanoparticles (MNP), to remove Cr 6+ ions. Each LR was added to an aqueous solution in which MNP were being synthesized by coprecipitation. Two composite adsorbents were obtained, with LR:MNP ratios of 1:1 and 3:1. The materials obtained were characterized by X-ray diffraction, scanning and transmission electron microscopy, and infrared and Raman spectroscopy. The results obtained showed that the laurel composite was the best adsorbent, reaching a maximum removal efficiency and capacity of 99.8 % and 30.5 mg/g, respectively. The optimal contact time was 30 min and the process fitted the Langmuir isotherm model, showing small effects of the fraction of sawdust residues used to support the MNP. Further studies will be performed to optimize the composition of the composites aiming to reduce the amount of costly MNP used while ensuring a high removal performance.